The Effect of Family Firm Image on Social Media Engagement Mediated by Brand Authenticity and Consumer-Company Identification (Case Study on Mamahke Jogja Company) - Ruth Yulia Pangesti; Bianka Andriyani (Indonesian Journal of Interdisciplinary Research in Science and Technology, 2023)
Purpose: This study aims to determine whether the image of a family company at the Mamahke Jogja company affects social media engagement with brand authentication and consumer-company identification as mediating variables. Methods: The method used in this study is the Structural Equation Model (SEM) Data analysis: Test validity, reliability test, structural model test, hypothesis testing and mediation test Result and discussions: The results show that family firm image has a positive effect on brand authenticity, brand authenticity has a positive effect on consumer-company identification, consumer-company identification has a positive effect on social media engagement Conclusion: The conclusion is that a good family firm image can indirectly increase interactions made by consumers who follow the company's Instagram.